The effect of value-added management on calf prices at superior livestock auction video markets - Zimmerman, Lance C.; Schroeder, Ted C.; Dhuyvetter, Kevin C.; Olson, K. C.; Stokka, Gerald L.; Seeger, J. T.; Grotelueschen, D. M. (My University, 2012)
Value-added management practices for cow-calf producers have become prevalent as feeders have recognized the value of calves raised with certified health and weaning programs. Export markets requiring age and source verification or non-hormone treated cattle and advancement of markets for naturally raised cattle have also presented profit opportunities for cow-calf producers. This study estimates the value of value-added calf production and marketing programs. Weaned steer calves sold with certified health programs realized $7 to $10 per cwt premiums. Age- and source-verified steers received $1 to $2 per cwt premiums exceeding added costs of about $0.67 per cwt in 2010 despite rapidly expanding supply.
Keywords: Feeder calf prices; Hedonic models; Value-added calf price